Metabolic Syndrome and Bipolar Disorder: What Should Psychiatrists Know? - de Almeida, Karla M. (CNS Neurosci Ther, 2011)
This paper reviews the association between bipolar disorder (BD) and metabolic syndrome (MetS), focusing on the etiopathogenetic and pathophysiological aspects of this association and on the recommendations for preventing and managing MetS in patients with BD. We conducted a nonsystematic literature review by means of a MEDLINE search. The exact causal relationship between MetS and BD is still uncertain. The side effects of psychotropic medications may be a major contributor to the increased rates of MetS in patients with BD. Other factors such as unhealthy lifestyles, common neuroendocrine and immuno‐inflammatory abnormalities, and genetic vulnerability may also play a role in explaining the high rates of MetS in BD. Strategies to prevent and treat the MetS and its cardiovascular consequences in patients with BD include accurate screening and monitoring of the patient and appropriate psychoeducation on weight control, healthy nutrition, and increased physical activity. When deciding on pharmacological therapy for the treatment of the components of the MetS, drug interactions and the effects of the medications on mood must be taken into account.